A multi-path chain kinetic reaction model to predict the evolution of 1, 1, 1-trichloroethane and its daughter products contaminant-plume in permeable reactive bio-barriers. (October 2019) - Wang, Wenbing; Wu, Yanqing
Abstract: Permeable reactive bio-barriers (Bio-PRBs) are a new and developing technique for in situ remediation of groundwater contamination. Some remediation technologies have often been impeded by insufficient understanding of contaminant transport and transformation in the subsurface environment. Therefore, advanced knowledge in contaminant transport and reactions in Bio-PRBs will be crucial to the successful practical application of this technique. A two-dimensional reaction model C1 was developed for predicting the multi-path chain kinetic reaction of 1, 1, 1-trichloroethane (1, 1, 1-TCA) in Bio-PRBs. This study demonstrates that model C1 is able to predict the 1, 1, 1-TCA breakthrough time and rapidly evaluate the Bio-PRBs retardation performance. The results show that microbial growth and immobilization are the key factors that affect the retardation and remediation performance of Bio-PRBs. The free growth of microorganisms had significant negative effects on hydraulic conductivity ( K ) in the zero-valent iron (ZVI) region of free microorganism Bio-PRBs (FM-PRBs). The total head loss in the FM-PRB was 9.0 cm, which was significantly greater than the head loss (6.5 cm) of immobilized microorganism Bio-PRBs (IM-PRBs). Compared to ZVI-PRBs and FM-PRBs, the numerical simulation results reveal that microbial immobilization significantly improves the remediation performance of IM-PRBs by 550.9% and 32.7%, respectively. The dual effect of microorganisms leads to significant differences in the 1, 1, 1-TCA and daughter products (1, 1-dichloroethane, 1, 1-dichloroethene, chloroethane and vinyl chloride) contaminant-plume evolution between FM-PRBs and IM-PRBs. In addition, model C1 can be utilized to design standard Bio-PRBs for real site of 1, 1, 1-TCA contanminated groundwater. To meet the safety standard of groundwater as potable water, the width of IM-PRBs needs to be increased by 24 cm. However, in FM-PRBs, the width needs to be increased by 42 cm. Therefore, IM-PRBs save costs significantly. This work has successfully used a model to optimize Bio-PRBs and to predict 1, 1, 1-TCA and daughter products contaminant-plume evolution in different Bio-PRBs. Graphical abstract: Image 1 Highlights: The different Bio-PRBs performance could be fast evaluated by the reaction model. Microorganism had dual effect on 1, 1, 1-TCA and daughter products contaminant-plume evolution. Microorganism immobilization was the critical step to improve Bio-PRBs performance. Multi-path reaction model could be as a tool to develop more cost-effective and competitive Bio-PRBs.